Selected Papers With Commentary of Tony Hilton Royle Skyrme - Brown Gerald E. (World Scientific, 1994)
The most important papers of Tony Hilton Royle Skyrme are collected in this volume which also includes commentaries by G. Brown, selected papers by Tony Skyrme and also articles related to the life as well as the work of Tony Skyrme, R. Dalitz, E. Witten and others. Skyrme's work provided an original solution to the problem of constructing fermions from bosons, formulating the topological soliton model of the nucleon. His two-parameter model of effective interactions in nuclei has yielded a remarkably accurate description of nuclear structure. His a-particle model of nuclei gave deep insights into the structure of important and complicated excited states. This volume is is intended for physicists working in the high energy, nuclear and mathematical physics community.